A2.29 Association of REL locus with rheumatoid arthritis susceptibility in Tunisian and French populations. (13th February 2015) - Khalifa, O; M'Madi, B; Balandraud, N; Lambert, N; Martin, M; Senechal, A; Genevieve, D; Picard, C; Lefranc, G; Pardoux, E; Mahjoub, T; Apparailly, F
Abstract : Background and objectives: Rheumatoid arthritis (RA) is a systemic autoimmune disease characterised by a chronic destructive inflammation in synovial joints. Genetic and environmental factors are likely to contribute etiologically to RA pathogenesis. Genome-wide association studies have identified dozen genes associated with RA among which REL, a member of the NF-kB family of transcription factors. A strong association at the REL locus was found in North American population. The present study aimed at investigating the association between 2 critical polymorphisms in the REL locus (rs13031237 and rs13017599) and RA susceptibility in two novel populations: Tunisian and French. In addition, the present study aimed at comparing the differences in genotypic distribution in both populations. Material and methods: A case–control study of 493 RA patients and 507 healthy controls age and sex matched was conducted in both Tunisian and French. All RA patients were ACPA positive. DNA was isolated from total blood using standard phenol chloroform method. All subjects were genotyped for both polymorphisms using a direct sequencing with the BigDye Terminator v3.1 Cycle Sequencing Kit (Applied Biosystems). The genotype distribution, haplotype analysis, and the linkage disequilibrium (LD) were analysed using the Bayesian method, and PLINK 1.07 and Haploview 4.2 softwares, respectively. Results: Only the genotype distribution of the rs13031237 polymorphism respected Hardy-Weinberg equilibrium, both in Tunisian and French populations. The association between REL rs13031237 polymorphism and RA susceptibility was found (p = 0.014), the genotype GG representing a protective factor for RA (OR = 0.46, 95% CI = 0.25–0.86). Linkage disequilibrium between both SNPs was strong (D = 53). There were 4 haplotypes with a frequency higher than 5%, constructed from the REL locus polymorphism. Haplotype H1 (TT), H3 (TC) and H4 (GC) were associated with increased risk for RA, whereas the haplotype H2 (GT) was significantly associated with a decreased risk for RA (p < 0.001). Analysis of the genotypic distribution of the rs13017599 polymorphism was however inconclusive. Finally correlation analyses with clinical and biological parameters are in progress. Conclusion: Our case-control study replicated for the first time the association of the rs13031237 at the REL locus with RA risk, in an independent cohort from Tunisia and France. We also identified haplotypes closely associated with disease risk.